Bioinspired Nanostructured Superwetting Thin-Films in a Self-supported form Enabled “Miniature Umbrella” for Weather Monitoring and Water Rescue - Li, Shan; Xiao, Peng; Zhou, Wei; Liang, Yun; Kuo, Shiao‑Wei; Chen, Tao (Nano-Micro Letters, 2021)
Two-dimensional (2D) soft materials, especially in their self-supported forms, demonstrate attractive properties to realize biomimetic morphing and ultrasensitive sensing. Although extensive efforts on design of self-supported functional membranes and integrated systems have been devoted, there still remains an unexplored regime of the combination of mechanical, electrical and surface wetting properties for specific functions. Here, we report a self-supported film featured with elastic, thin, conductive and superhydrophobic characteristics. Through a well-defined surface modification strategy, the surface wettability and mechanical sensing can be effectively balanced. The resulted film can function as a smart umbrella to achieve real-time simulated raining with diverse frequencies and intensity. In addition, the integrated umbrella can even response sensitively to the sunlight and demonstrate a positively correlation of current signals with the intensity of sun illumination. Moreover, the superhydrophobic umbrella can be further employed to realize water rescue, which can take the underwater object onto water surface, load and rapidly transport the considerable weight. More importantly, the whole process of loaded objects and water flow velocity can be precisely detected. The self-supported smart umbrella can effectively monitor the weather and realize a smart water rescue, demonstrating significant potentials in multifunctional sensing and directional actuation in the presence of water. Highlights: 1 An elastic, superhydrophobic and conductive thin film inspired by the natural self-supported superhydrophobic butterfly wings enabled by a controllable composite of assembled carbon nanotube and elastomer is fabricated. 2 Through the adjustment of hydrophobic elastomeric coating, the surface wettability can be effectively controlled and still maintain superhydrophobic characteristics under the applied strain of 60%. 3 The achieved film can function as a self-supported smart umbrella to sensitively monitor the day weather and perform water rescue